Plan de medios digitales para la promoción de los atractivos turísticos de la parroquia urbana Catacocha, provincia de Loja. - Encarnación Díaz, Teresa Paola (2024)
By integrating tourism with technology, accessibility to tourist destinations can be improved. However, lack of promotion has led to historical places being forgotten. The Catacocha Parish, despite being declared Cultural Heritage, lacks adequate broadcasting. Therefore, it is important to consider implementing a digital media plan to address this issue. The general objective of this work is to develop a digital media plan in order to promote the tourist attractions of Catacocha. Two specific objectives were established: first, determine the current situation of the digital media through which the tourist promotion of the Parish is carried out. To do this, a summary sheet of tourist attractions was used and an internal and external audit of the website was carried out with tools such as Semrush, SEO (Search Engine Optimization) Check and Pagespeed, revealing that this page is not working well. Regarding social networks, a detailed analysis was carried out by counting the publications, calculating their engagement and examining the content managed, observing a lack of tourism focus. In addition, interviews were conducted with the person in charge of the Tourism department and local actors. The results obtained were used to perform a SWOT analysis and structure a buyer person profile. The second objective was to propose a digital media plan to disseminate the attractions of the parish. This plan was structured based on objectives, content, budget, schedule, evaluation and monitoring. In conclusion, it was found that both the Decentralized Autonomous Government (GAD) of Paltas website and social networks need to implement more interactive content focused on tourism.